THE USE OF ALBIZIA FALCATARIA WITH CONDENSED TANNIN CONTENT ON IN VITRO GAS PRODUCTION AND RUMINAL FERMENTATION - A. Afzalani,; R. A. Muthalib,; R. Dianita, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed  to evaluate  Albizia falcataria with condensed tannin content in the diets on gas production and ruminal fermentation parameters. A completely randomized design (CRD) with fours treatment and five replications had applied in this study. The treatment in this study was fours combined of Brachiaria mutica and Albizia falcataria namely; R0: 60% Brachiaria mutica (BM) + 0% Albizia falcataria (AF) + 40% concentrate (CON), R1: 50% BM + 10% AF + 40% CON, R2: 40% BM + 20% AF + 40% CON and R3: 30% BM + 30% AF + 40% CON. The concentrate formulated using feed ingredients consists of 58% rice bran, 15% soybean cake meal, 30% corn, 1% salt, and 1% multi-vitamin minerals. The Diets samples were  incubated at 39oC. The volume of gas and CH4 were recorded manually at 3, 6, 9, 12, 24, and 48 h post-incubation. Dry matter digestibility (DMD), organic matter digestibility (OMD), pH, N-ammonia (N-NH3), protozoa count, and microbial protein production (MP) were measured at 48 h post-incubation. The study showed that increased use of AF decreases (P